2001
DOI: 10.1034/j.1399-6576.2001.450206.x
|View full text |Cite
|
Sign up to set email alerts
|

Warning! Suctioning. A lung model evaluation of closed suctioning systems

Abstract: CSS should not be used in volume control ventilation due to risk of high intrinsic PEEP levels at insertion of the catheter and extreme negative pressures during suctioning. Pressure control ventilation produces less intrinsic PEEP effect. The continuous positive airway pressure (CPAP) mode offers the least intrinsic PEEP during insertion of the catheter and least sub-atmospheric pressure during suctioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 13 publications
3
36
0
1
Order By: Relevance
“…This effect may be particularly important with infant ETTs, as this space is relatively small. Studies comparing airway pressures during open and closed suction using adult-sized equipment have reported higher pressures with closed suction than with open, at least under similar conditions to our study (4,10). These findings suggest that the larger area between the adult ETT and catheter may allow for flow to be predominantly laminar despite the dynamic flow conditions of closed suction, and therefore pressure loss to be less than with ETTs used for infants.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This effect may be particularly important with infant ETTs, as this space is relatively small. Studies comparing airway pressures during open and closed suction using adult-sized equipment have reported higher pressures with closed suction than with open, at least under similar conditions to our study (4,10). These findings suggest that the larger area between the adult ETT and catheter may allow for flow to be predominantly laminar despite the dynamic flow conditions of closed suction, and therefore pressure loss to be less than with ETTs used for infants.…”
Section: Discussionsupporting
confidence: 66%
“…Airway pressures during closed suction are influenced by ventilation mode in adult models (4,10), but this effect has not been studied using neonatal ventilators. Of particular interest is the performance of closed suction catheters during highfrequency oscillatory ventilation (HFOV), because closed suction is generally recommended for patients receiving this ventilation mode (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…51 However a number of studies have cautioned clinicians about negative pressures associated with the use of closed suction units and a reduction in secretion clearance particularly in paediatrics. [52][53][54] Consequently, the use of closed suction systems, at least in the paediatric population, remains questionable. In addition, saline instillation exacerbates gas maldistribution and worsens de-recruitment by increasing threshold opening pressures.…”
Section: When Do You Recruit Lungs?mentioning
confidence: 99%
“…In addition, saline instillation exacerbates gas maldistribution and worsens de-recruitment by increasing threshold opening pressures. [51][52] Recent studies measured the impact of various suctioning methods and modes of ventilation and found that irrespective of ventilation mode, or whether open or closed suctioning was used, a significant loss of FRC occurred. [48][49][50][51] In a study by Lindgren et al, FRC as measured by EIT decreased by 58±24% of baseline after disconnection of the endotracheal tube and a further 22±10% during open suction itself.…”
Section: When Do You Recruit Lungs?mentioning
confidence: 99%